THE EFFECT OF ADMINISTRATING AZOLLA THROUGH DRINKING WATER ON BROILER PERFORMANCE - I K. C., Negara; Siti, N.W.; Wibawa, A.A.P.P. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of giving azolla extract through drinking water on broiler performance. This research was conducted in Yangapi Village, Tembuku District, Bangli Regency for 5 weeks from December 2022 to January 2023. This study used a Completely Randomized Design (CRD) which consisted of four treatments, four replicates and each replicate consisted of four rats. broiler with an average initial weight of 159.63g + 7.98. The treatments given were broilers given drinking water without azolla extract (P0), broilers given 2% azolla extract via drinking water (P1), broilers given 4% azolla extract via drinking water (P2), and broilers given 6% extract. azolla through drinking water (P3). The variables observed included initial body weight, ration consumption, drinking water consumption, final body weight, body weight gain and feed conversion ratio. The results of research on the administration of azolla extract 2% 4% 6% average ration consumption, drinking water consumption, body weight gain, and FCR values ??did not give significant results (P> 0.05). Based on the results of this study it can be concluded that giving azolla extract through drinking water on broiler performance as much as 2% 4% and 6% cannot improve broiler performance.